Numerical investigation of the aerodynamic noise mechanism in high-speed trains operating at 400 km/h - Junhui Huang; Weishuang Lu; Zhenxu Sun; Prasert Prapamonthon; Dilong Guo; Guowei Yang; Zhenan Song; Wenlin Hu; Sha Huang (AIP Advances, 2025)
In this study, an improved delayed detached eddy simulation in conjunction with the Ffowcs Williams–Hawkings acoustic analogy is used to numerically compare the aerodynamic noise characteristics of the CR400BF and CR450 high-speed trains operating at 350 and 400 km/h, respectively. The results show that although there are noticeable changes in the distribution of acoustic energy, increasing the operating speed to 400 km/h has no discernible effect on the locations of the main noise sources. The airflow characteristics are optimized by using streamlined front designs, bogie web plates, and fully enclosed skirts, resulting in reduced turbulent kinetic energy and pressure fluctuations. As a result, the noise amplitude in the front car region is effectively reduced, while the formation of small-scale vortices, which can cause noise at high frequencies, is inhibited. However, because of the smoothing of the underbody and the lack of bogie web plates in the middle sections, higher airflow velocities are introduced, intensifying the interaction with the third and fourth bogies. This leads to the increase in noise amplitudes in these regions.
Keywords: Aerodynamics and Fluid Dynamics Research; Aerodynamics and Acoustics in Jet Flows; Wind and Air Flow Studies